One species does not replace a community: functional roles of co-occurring translocated and endemic mycophagous mammals - A. Naccarella; C. Truong; E. G. Ritchie; D. R. Sutherland; A. Coetsee; A. R. Rendall (Oecologia, 2026)
Biodiversity decline alters species interaction networks and can destabilise ecosystem functions. Fungal consumption by mammals supports ectomycorrhizal (ECM) spore dispersal, contributing to fungi-plant symbioses. The ecological impacts of losing mycophagous mammals and to what extent species roles are redundant or complementary remains poorly quantified. Using fungal ITS2 metabarcoding, we explore the fungal community in scats of a translocated fungal generalist, the eastern barred bandicoot ( Perameles gunnii ), on Phillip and French Island in southeast Australia. We compare: (1) fungi in bandicoot scats and soil; (2) soil fungi, soil properties and vegetation to compare possible fungal availability across habitats; and (3) fungi within the scats of two sympatric mammals, an endemic fungal generalist (swamp wallaby, Wallabia bicolor , on Phillip Island) and fungal specialist (long-nosed potoroo, Potorous tridactylus trisulcatus , on French Island). We found diverging patterns between soil fungi and mammal diet; and between soil fungi, soil properties and vegetation across sites. On French Island, bandicoot and potoroo scats had similar ECM fungal richness, although community composition differed, with less ECM observed in soils. On Phillip Island, only one scat from the wallaby contained ECM fungi, while soils were more ECM diverse than bandicoot scat. Our findings suggest the functional roles of mycophages should not be considered interchangeable across ecosystems. Translocated bandicoots may have the capacity to perform functionally unique roles compared to resident mycophages, highlighting that translocations could provide multiple ecosystem benefit. Adequately assessing functional redundancy or complementarity requires a site-specific characterisation and comparison of the cumulative roles of co-occurring mycophagous mammals.

Mycophagy varies at individual-, population- and site- levels in the diet of a translocated mammal across multiple safe havens - A. Naccarella; C. Truong; E. G. Ritchie; D. R. Sutherland; A. Coetsee; A. R. Rendall (Biodiversity and Conservation, 2026)
Restoring ecosystem functions via conserving and translocating threatened species is an increasingly common conservation action and priority. Monitoring how a translocated species interacts with the recipient ecosystem and co-occurring species is rarely the focus of strategic management plans. Digging, mycophagous mammals play critical ecosystem roles including bioturbation and fungal spore dispersal. The fungal diets of translocated digging-mycophagous mammals have rarely been investigated across translocation sites. We examined the endangered eastern barred bandicoot ( Perameles gunnii ) as a case study to compare the ecological role of a generalist mycophagous mammal that has been translocated to multiple sites inside and outside their historic range for conservation purposes in Australia. We characterized fungal assemblages in 91 bandicoot scats across five sites, two inside and three outside the species historic range, using ITS2 metabarcoding. Despite low sample size, our data suggested fungal richness and community composition varied at individual-, population- and site- levels, aligning with the opportunistic and generalist dietary niche of bandicoots. We found no clear trends between fungal richness or community composition with vegetation attributes. Our study highlights the need to understand how mammal-fungi interactions vary across spatial-scales and population-levels to better predict possible ecological impacts of conservation translocations and restoration attempts. We highlight the challenges of studying environmental drivers of mycophagy in modified landscapes, particularly with limited reference ecosystems. We therefore encourage integrated and explicit monitoring of key species interactions at an individual-, population- and site-level to better understand synergies between translocations for species conservation and the reinstatement of ecosystem functions.

Role of funders in embedding tests in conservation practice - Rebecca K. Smith; Nancy Ockendon; Nida Al‐Fulaij; Alessandro Badalotti; Rachel Beattie; James Byrne; Sophia Cooke; Tiago de Zoeten; Winifred F. Frick; Stephan M. Funk; Douglas Gibbs; Lauren Gupta; et al. (Conservation Biology, 2026)
Effective conservation practice requires decisions based on reliable and relevant evidence, but significant gaps in the evidence base exist. Incorporating well‐designed tests of the effectiveness of interventions for biodiversity in conservation projects is one of the best ways to scale up the rate of evidence generation. Funders of conservation projects are uniquely positioned to support and incentivize such tests as part of the grant‐making process. Using a structured process, as 25 conservation funders and members of Conservation Evidence, we identified means of improving the effectiveness of the work funded through the support of enhanced evidence generation. We identified 11 approaches through which funders can support embedding testing, ranging from encouraging inclusion of a test in the project proposal, to designating separate funds for incorporating a test, to supporting an external testing unit to provide training and advice. The appropriate approaches vary depending on the scale, process, and type of funding. Barriers to supporting testing and potential solutions were discussed, barriers such as a lack of skills to check tests are appropriate and well designed and the additional time needed to develop, implement, and see outcomes of tests and differing types of projects. By encouraging testing of actions as part of conservation practice (where appropriate), funders will ultimately facilitate a stronger evidence base for more effective decision‐making and better outcomes for nature and society.

A horizon scan of biological conservation issues for 2026 - William J. Sutherland; Stuart H.M. Butchart; Stewart J. Clarke; Nigel R. Doar; Helen Doran; Imogen C. Douglas; Daniel J. Field; Erica Fleishman; Kevin J. Gaston; James E. Herbert-Read; Alice C. Hughes; Hermanni Kaartokallio; et al. (Trends in Ecology & Evolution, 2026)

Generation of a Ym1 deficient mouse utilising CRISPR-Cas9 in CB6 embryos - J. E. Parkinson; G. E. Baldwin; P. H. Papotto; N. E. Humphreys; A. J. Day; A. D. Adamson; J. E. Allen; T. E. Sutherland (Transgenic Research, 2025)
Chitinase-like proteins (CLPs) are of wide interest due to their significant roles during both homeostatic and pathological processes. Human CLPs such as YKL-40 have been proposed as biomarkers of disease severity in many conditions. Murine CLPs Brp39, Ym1, and Ym2 are similarly upregulated in multiple mouse models of pathology. Investigation of Ym1 and Ym2 is hampered by recent gene duplication events on the C57BL/6, but not BALB/c, background leading to complexity in the genomic locus. Here, we have generated a Ym1 deficient mouse using a novel CRISPR-Cas9 targeting approach involving CB6 (C57BL/6 X BALB/c) mixed background embryos. Validation using flow cytometry, ELISA, and immunofluorescence confirmed no expression of mature Ym1 protein. Additionally, expression of related genes including Chia, Chil1, and Chil4 were not altered in Ym1-deficent animals. This new transgenic mouse line will be key for future investigations of CLP functions and the utilised approach to genetic manipulation may provide a useful strategy for other genes which show differences in copy number between inbred mouse strains.

Open atrial septal defect repair in a dog using fresh autologous pericardium - B.J. Sutherland; M. Kraus; C. Barr; L. Aronson; D. Holt; S. Fuller (Journal of Veterinary Cardiology, 2025)

Estuarine Sediment Dynamics and the Importance of Storms in Moving (and Removing) Mud - Molly E. Keogh; David A. Sutherland; Emily F. Eidam; Tyler D. Souza; Jenni Schmitt; Alicia Helms; David K. Ralston (Estuaries and Coasts, 2025)

Being ghosted: determining the progenitor genomes and biogeographic origin of the invasive fern giant salvinia - Erin M. Sigel; Jonas I. Mendez-Reneau; Brittany L. Sutherland; Pedro Bond Schwartsburd; Stacy D. Holt; James B. Beck (Biological Invasions, 2025)

Corrigendum to: “Nanodisc assembly from bacterial total lipid extracts” [Chem. Phys. Lipids (2024) 105425] - Trent R. Llewellyn; Olivia R.C. Pimentel; Kiersten D. Lenz; Makaela M. Montoya; Jessica Z. Kubicek-Sutherland (Chemistry and Physics of Lipids, 2025)

A horizon scan of biological conservation issues for 2025 - William J. Sutherland; Peter N.M. Brotherton; Holly M. Butterworth; Stewart J. Clarke; Tammy E. Davies; Nigel Doar; Nafeesa Esmail; Erica Fleishman; Kevin J. Gaston; James E. Herbert-Read; Alice C. Hughes; Jonathan Hughes; et al. (Trends in Ecology & Evolution, 2025)

Evaluating the sensitivity of a chronic plant bioassay relative to an independently derived predicted no-effect thresholds to support risk assessment of very hydrophobic organic chemicals - Aaron D. Redman; Miriam Leon Paumen; Daniel J. Letinski; Barbara A. Kelley; Cary Sutherland; Bryan M. Hedgpeth; Josh D. Butler; Roger Prince; Gail E. Bragin; Abraham J. Smith (Archives of Environmental Contamination and Toxicology, 2025)

Imperiled wanderlust lichens in steppe habitats of western North America comprise geographically structured mycobiont lineages and a reversal to sexual reproduction within this asexual clade - Robert Hadfield; Teagan Mulford; Makani L. Fisher; Abigail Borgmeier; Diego A. Ardon; Andrew D. Suchomel; Judicaël Fomekong-Lontchi; Laura Sutherland; Madison Huie; Pungki Lupiyaningdyah; Sierra Nichols; Ying Fei Lin; et al. (Molecular Phylogenetics and Evolution, 2024)

Spatial and Temporal Variability of Century-Scale Sediment Accumulation in an Active-Margin Estuary - Emily Eidam; T. Souza; M. Keogh; D. Sutherland; D. K. Ralston; J. Schmitt; A. Helms (Estuaries and Coasts, 2024)

Soil solarisation delivers near zero levels of Fusarium pseudograminearum in cereal crown rot reference sites - Prue Bottomley; Mark W. Sutherland; Bree A.L. Wilson; Bethany Rognoni; Alison Kelly; Cassandra D. Percy (Crop Protection, 2024)

Nanodisc assembly from bacterial total lipid extracts - Trent R. Llewellyn; Olivia R.C. Pimentel; Kiersten D. Lenz; Makaela M. Montoya; Jessica Z. Kubicek-Sutherland (Chemistry and Physics of Lipids, 2024)

Abundance of Vibrio aestuarianus, water temperature, and stocking density are associated with summer mortality of Pacific oysters in suspended culture - M. W. Cowan; C. M. Pearce; T. J. Green; T. Finston; G. R. Meyer; B. McAmmond; J. D. Van Hamme; E. M. Bottos; R. Marshall; W. Evans; T. F. Sutherland; P. Y. de la Bastide (Aquaculture International, 2024)
High mortality rates of cultured Pacific oysters ( Crassostrea gigas ) during the summer months have regularly occurred on oyster farms in British Columbia, Canada over the last 10 years, but little is known about the microbial and environmental conditions that contribute to such mortality events. The objective of the study was to determine correlative factors associated with the onset of a summer mortality event in oysters (mean ± SD shell height: 14.2 ± 0.5 mm) grown in suspended culture at four stocking densities (150, 300, 450, 600 oysters tray −1 ) from May 11 to September 17, 2018. Variables examined included both biotic (oyster growth, mortality, reproductive development, and microbiome (approximately every week); Vibrio and harmful algal species abundance) and abiotic (temperature, salinity, turbidity, dissolved oxygen, p CO 2 , pH, and aragonite saturation) ones. Both the absolute abundance of V. aestuarianus and the relative abundance of Vibrio spp. increased with observed oyster mortality and declining health. Mortality was highest on August 12 and associated with a prior period of elevated temperatures (i.e., increasing temperatures from early July to early August) and increased oyster growth/reproductive development. At that time, systemic mixed microbial infections and necrotic gill tissue in histological cross sections were observed in 19% of oysters that appeared healthy macroscopically. Cumulative percent mortalities per tray ranged from 34 to 75%, the highest-density trays having significantly less mortality and smaller shell width, shell length, and gonad length than lower-density trays. This study demonstrates the significant impact of summer mortality on Pacific oysters and highlights the biotic (host growth, reproductive development, and microbiome composition as well as Vibrio spp. abundance) and abiotic (water temperature) factors associated with the observed mortality in this region.

Sensing Pre- and Post-Ecdysis of Tropical Rock Lobsters, Panulirus ornatus, Using a Low-Cost Novel Spectral Camera - Charles Sutherland; Alan D. Henderson; Dean R. Giosio; Andrew J. Trotter; Greg G. Smith (Journal of Marine Science and Engineering, 2024)
Tropical rock lobsters (Panulirus ornatus) are a highly cannibalistic species with intermoult animals predominantly attacking animals during ecdysis (moulting). Rapid, positive characterisation of pre-ecdysis lobsters may open a pathway to disrupt cannibalism. Ecdysial suture line development is considered for pre-ecdysis recognition with suture line definition compared for intermoult and pre-ecdysis lobsters emerged and immerged, using white, near ultraviolet (365 nm), near infrared (850 nm), and specialty SFH 4737 broadband IR LEDs against a reference of intermoult lobsters with no suture line development. Difficulties in acquiring suture line images prompted research into pre-ecdysis characterisation from the lobster’s dorsal carapace, due to its accessibility through a culture vessel’s surface. In this study, a novel low-cost spectral camera was developed by coordinating an IMX219 image sensor, an AS7265x spectral sensor, and four SFH 4737 broadband infrared LEDs through a single-board computer. Images and spectral data from the lobster’s dorsal carapace were acquired from intermoult, pre-ecdysis, and post-ecdysis lobsters. For the first time, suture line definition was found to be enhanced under 850 nm, 365 nm, and SFH 4737 LEDs for immerged lobsters, while the 850 nm LED achieved the best suture line definition of emerged lobsters. Although the spectral camera was unable to characterise pre-ecdysis, its development was validated when a least squares regression for binary classification decision boundary successfully separated 86.7% of post-ecdysis lobsters. Achieving post-ecdysis characterisation is the first time the dorsal carapace surface has been used to characterise a moult stage for palinurid lobsters.

Increases in regional brain volume across two native South American male populations - Nikhil N. Chaudhari; Phoebe E. Imms; Nahian F. Chowdhury; Margaret Gatz; Benjamin C. Trumble; Wendy J. Mack; E. Meng Law; M. Linda Sutherland; James D. Sutherland; Christopher J. Rowan; L. Samuel Wann; Adel H. Allam; et al. (GeroScience, 2024)
Industrialized environments, despite benefits such as higher levels of formal education and lower rates of infections, can also have pernicious impacts upon brain atrophy. Partly for this reason, comparing age-related brain volume trajectories between industrialized and non-industrialized populations can help to suggest lifestyle correlates of brain health. The Tsimane, indigenous to the Bolivian Amazon, derive their subsistence from foraging and horticulture and are physically active. The Moseten, a mixed-ethnicity farming population, are physically active but less than the Tsimane. Within both populations ( N = 1024; age range = 46–83), we calculated regional brain volumes from computed tomography and compared their cross-sectional trends with age to those of UK Biobank (UKBB) participants ( N = 19,973; same age range). Surprisingly among Tsimane and Moseten (T/M) males, some parietal and occipital structures mediating visuospatial abilities exhibit small but significant increases in regional volume with age. UKBB males exhibit a steeper negative trend of regional volume with age in frontal and temporal structures compared to T/M males. However, T/M females exhibit significantly steeper rates of brain volume decrease with age compared to UKBB females, particularly for some cerebro-cortical structures (e.g., left subparietal cortex). Across the three populations, observed trends exhibit no interhemispheric asymmetry. In conclusion, the age-related rate of regional brain volume change may differ by lifestyle and sex. The lack of brain volume reduction with age is not known to exist in other human population, highlighting the putative role of lifestyle in constraining regional brain atrophy and promoting elements of non-industrialized lifestyle like higher physical activity.

Population genomics of harbour seal Phoca vitulina from northern British Columbia through California and comparison to the Atlantic subspecies - Ben J. G. Sutherland; Claire Rycroft; Ashtin Duguid; Terry D. Beacham; Strahan Tucker (Molecular Ecology, 2024)
The harbour seal Phoca vitulina is a ubiquitous pinniped species found throughout coastal waters of the Northern Hemisphere. Harbour seal impacts on ecosystem dynamics may be significant due to their high abundance and food web position. Two subspecies exist in North America, P. v. richardii in the Pacific Ocean and P. v. vitulina in the Atlantic. Strong natal philopatry of harbour seals can result in fine‐scale genetic structure and isolation by distance. Management of harbour seals is expected to benefit from improved resolution of seal population structure and dynamics. Here, we use genotyping‐by‐sequencing to genotype 146 harbour seals from the eastern Pacific Ocean (i.e. British Columbia (BC), Oregon and California) and the western Atlantic Ocean (i.e. Québec, Newfoundland and Labrador). Using 12,742 identified variants, we confirm the recently identified elevated genetic diversity in the eastern Pacific relative to the western Atlantic and greatest differentiation between the subspecies. Further, we demonstrate that this is independent of reference genome bias or other potential technical artefacts. Coast‐specific analyses with 8933 and 3828 variants in Pacific and Atlantic subspecies, respectively, identify divergence between BC and Oregon–California, and between Québec and Newfoundland–Labrador. Unexpected PCA outlier clusters were observed in two populations due to cryptic relatedness of individuals; subsequently, closely related samples were removed. Admixture analysis indicates an isolation‐by‐distance signature where Oregon seals contained some of the BC signature, whereas California did not. Additional sampling is needed in the central and north coast of BC to determine whether a discrete separation of populations exists within the region.

A horizon scan of global biological conservation issues for 2024 - William J. Sutherland; Craig Bennett; Peter N.M. Brotherton; Stuart H.M. Butchart; Holly M. Butterworth; Stewart J. Clarke; Nafeesa Esmail; Erica Fleishman; Kevin J. Gaston; James E. Herbert-Read; Alice C. Hughes; Jennifer James; et al. (Trends in Ecology & Evolution, 2024)

What is Salvinia molesta (Salviniaceae)? Determining the maternal progenitor and genetic diversity of the clonal invasive fern giant salvinia - Stacy D. Holt; Erin M. Sigel; Brittany L. Sutherland; Pedro Bond Schwartsburd; James B. Beck (Biological Invasions, 2023)

Evaluating the impact of caribou habitat restoration on predator and prey movement - Melanie Dickie; Geoff G. Sherman; Glenn D. Sutherland; Robert S. McNay; Michael Cody (Conservation Biology, 2023)
Fragmentation of the boreal forest by linear features, including seismic lines, has destabilized predator–prey dynamics, resulting in the decline of woodland caribou ( Rangifer tarandus caribou ) populations. Restoration of human‐altered habitat has therefore been identified as a critical management tool for achieving self‐sustaining woodland caribou populations. However, only recently has testing of the response of caribou and other wildlife to restoration activities been conducted. Early work has centered around assessing changes in wildlife use of restored seismic lines. We evaluated whether restoration reduces the movement rates of predators and their associated prey, which is expected to decrease predator hunting efficiency and ultimately reduce caribou mortality. We developed a new method for using cameras to measure fine‐scale movement by measuring speed as animals traveled between cameras in an array. We used our method to quantify speed of caribou, moose ( Alces alces ), bears ( Ursus americanus ), and wolves ( Canis lupus ) on treated (restored) and untreated seismic lines. Restoration treatments reduced travel speeds along seismic lines of wolves by 1.38 km/h, bears by 0.55 km/h, and caribou by 1.57 km/h, but did not reduce moose travel speeds. Reduced predator and caribou speeds on treated seismic lines are predicted to decrease encounter rates between predators and caribou and thus lower caribou kill rates. However, further work is needed to determine whether reduced movement rates result in reduced encounter rates with prey, and ultimately reduced caribou mortality.

Relationship between in feed drugs, antibiotics and organic enrichment in marine sediments at Canadian Atlantic salmon aquaculture sites - M.V. Kingsbury; D. Hamoutene; P. Kraska; A. Lacoursière-Roussel; F. Page; T. Coyle; T. Sutherland; O. Gibb; C.W. Mckindsey; F. Hartog; S. Neil; K. Chernoff; et al. (Marine Pollution Bulletin, 2023)

Foresight science in conservation: Tools, barriers, and mainstreaming opportunities - Gabrielle Ednie; Tyreen Kapoor; Olga Koppel; Morgan L. Piczak; Jessica L. Reid; Alyssa D. Murdoch; Carly N. Cook; William J. Sutherland; Steven J. Cooke (Ambio, 2023)

A global biological conservation horizon scan of issues for 2023 - William J. Sutherland; Craig Bennett; Peter N.M. Brotherton; Holly M. Butterworth; Mick N. Clout; Isabelle M. Côté; Jason Dinsdale; Nafeesa Esmail; Erica Fleishman; Kevin J. Gaston; James E. Herbert-Read; Alice Hughes; et al. (Trends in Ecology & Evolution, 2023)

Geographical contrasts of Y‐chromosomal haplogroups from wild and domestic goats reveal ancient migrations and recent introgressions - Isaäc J. Nijman; Benjamin D. Rosen; Philippe Bardou; Thomas Faraut; Tristan Cumer; Kevin G. Daly; Zhuqing Zheng; Yudong Cai; Hojjat Asadollahpour; Bengi Çınar Kul; Wei‐Yi Zhang; Guangxin E.; et al. (Molecular Ecology, 2022)
By their paternal transmission, Y‐chromosomal haplotypes are sensitive markers of population history and male‐mediated introgression. Previous studies identified biallelic single‐nucleotide variants in the SRY , ZFY and DDX3Y genes, which in domestic goats identified four major Y‐chromosomal haplotypes, Y1A, Y1B, Y2A and Y2B, with a marked geographical partitioning. Here, we extracted goat Y‐chromosomal variants from whole‐genome sequences of 386 domestic goats (75 breeds) and seven wild goat species, which were generated by the VarGoats goat genome project. Phylogenetic analyses indicated domestic haplogroups corresponding to Y1B, Y2A and Y2B, respectively, whereas Y1A is split into Y1AA and Y1AB. All five haplogroups were detected in 26 ancient DNA samples from southeast Europe or Asia. Haplotypes from present‐day bezoars are not shared with domestic goats and are attached to deep nodes of the trees and networks. Haplogroup distributions for 186 domestic breeds indicate ancient paternal population bottlenecks and expansions during migrations into northern Europe, eastern and southern Asia, and Africa south of the Sahara. In addition, sharing of haplogroups indicates male‐mediated introgressions, most notably an early gene flow from Asian goats into Madagascar and the crossbreeding that in the 19th century resulted in the popular Boer and Anglo‐Nubian breeds. More recent introgressions are those from European goats into the native Korean goat population and from Boer goat into Uganda, Kenya, Tanzania, Malawi and Zimbabwe. This study illustrates the power of the Y‐chromosomal variants for reconstructing the history of domestic species with a wide geographical range.

Interactive Effects of HIV Infection and Cannabis Use on Insula Subregion Functional Connectivity - Jessica S. Flannery; Michael C. Riedel; Taylor Salo; Lauren D. Hill-Bowen; Ranjita Poudel; Ashley R. Adams; Angela R. Laird; Raul Gonzalez; Matthew T. Sutherland (Journal of Neuroimmune Pharmacology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Mapping the Shoreface of Coastal Sediment Compartments to Improve Shoreline Change Forecasts in New South Wales, Australia - M. A. Kinsela; D. J. Hanslow; R. C. Carvalho; M. Linklater; T. C. Ingleton; B. D. Morris; K. M. Allen; M. D. Sutherland; C. D. Woodroffe (Estuaries and Coasts, 2022)
The potential response of shoreface depositional environments to sea level rise over the present century and beyond remains poorly understood. The shoreface is shaped by wave action across a sedimentary seabed and may aggrade or deflate depending on the balance between time-averaged wave energy and the availability and character of sediment, within the context of the inherited geological control. For embayed and accommodation-dominated coastal settings, where shoreline change is particularly sensitive to cross-shore sediment transport, whether the shoreface is a source or sink for coastal sediment during rising sea level may be a crucial determinant of future shoreline change. While simple equilibrium-based models (e.g. the Bruun Rule) are widely used in coastal risk planning practice to predict shoreline change due to sea level rise, the relevance of fundamental model assumptions to the shoreface depositional setting is often overlooked due to limited knowledge about the geomorphology of the nearshore seabed. We present high-resolution mapping of the shoreface-inner shelf in southeastern Australia from airborne lidar and vessel-based multibeam echosounder surveys, which reveals a more complex seabed than was previously known. The mapping data are used to interpret the extent, depositional character and morphodynamic state of the shoreface, by comparing the observed geomorphology to theoretical predictions from wave-driven sediment transport theory. The benefits of high-resolution seabed mapping for improving shoreline change predictions in practice are explored by comparing idealised shoreline change modelling based on our understanding of shoreface geomorphology and morphodynamics before and after the mapping exercise.

A Pragmatic Approach for Developing Landbase Cumulative Effects Assessments with Aggregated Impacts Crossing Multiple Ecological Values - Glenn D. Sutherland; Jason Smith; F. Louise Waterhouse; Sari C. Saunders; Kathy Paige (Environmental Management, 2022)
In strategic cumulative effects assessments, significant methodological challenges exist for classifying and aggregating impacts when using multiple indicators to determine relative risks upon ecological values from anthropogenic developments. We present a strategic spatial modeling case study CEA (2012–2112) in a 909,000 ha forested landscape of Southwestern British Columbia. We explore decisions needed to calculate and aggregate modeled indicators of cumulative anthropogenic footprints on landscape conditions by examining the choice of quantitative methods. We compare how aggregated impact conclusions may differ for seven indicators grouped in two ways to represent three ecological values (Forest Ecosystems, Riparian Ecosystems and Species at Risk): four expert-defined policy-driven valued components (VCs) or three analytically derived environmental resource factors (ERFs). By explicitly demonstrating methodological choices at each step of impact estimation and aggregation, we outline a practical systematic approach to customize strategic CEAs of this type and retain transparency for interpreting impacts among values. Aggregated impacts for VCs appeared dominated by those estimated from “condition” indicators describing the degree of expected deviations in indicator states from desired conditions; aggregated impacts of ERFs were dominated by “pressure” indicators linked to underlying causal processes assumed important for describing changes in future ecological conditions. High spatial congruence occurred between impact statements for some VCs compared to ERFs representing the same ecological value; poor congruence between others likely occurred because they represented different ecological processes. Aggregated impact classifications may usefully signal impact severity and risk but are dependent on indicator grouping, hence choices for aggregation are integral to the assessment process.

A quantitative global review of species population monitoring - Caroline Moussy; Ian J. Burfield; P. J. Stephenson; Arabella F. E. Newton; Stuart H. M. Butchart; William J. Sutherland; Richard D. Gregory; Louise McRae; Philip Bubb; Ignacio Roesler; Cynthia Ursino; Yanqing Wu; et al. (Conservation Biology, 2022)
Species monitoring, defined here as the repeated, systematic collection of data to detect long‐term changes in the populations of wild species, is a vital component of conservation practice and policy. We created a database of nearly 1200 schemes, ranging in start date from 1800 to 2018, to review spatial, temporal, taxonomic, and methodological patterns in global species monitoring. We identified monitoring schemes through standardized web searches, an online survey of stakeholders, in‐depth national searches in a sample of countries, and a review of global biodiversity databases. We estimated the total global number of monitoring schemes operating at 3300–15,000. Since 2000, there has been a sharp increase in the number of new schemes being initiated in lower‐ and middle‐income countries and in megadiverse countries, but a decrease in high‐income countries. The total number of monitoring schemes in a country and its per capita gross domestic product were strongly, positively correlated. Schemes that were active in 2018 had been running for an average of 21 years in high‐income countries, compared with 13 years in middle‐income countries and 10 years in low‐income countries. In high‐income countries, over one‐half of monitoring schemes received government funding, but this was less than one‐quarter in low‐income countries. Data collection was undertaken partly or wholly by volunteers in 37% of schemes, and such schemes covered significantly more sites and species than those undertaken by professionals alone. Birds were by far the most widely monitored taxonomic group, accounting for around half of all schemes, but this bias declined over time. Monitoring in most taxonomic groups remains sparse and uncoordinated, and most of the data generated are elusive and unlikely to feed into wider biodiversity conservation processes. These shortcomings could be addressed by, for example, creating an open global meta‐database of biodiversity monitoring schemes and enhancing capacity for species monitoring in countries with high biodiversity. Article impact statement : Species population monitoring for conservation purposes remains strongly biased toward a few vertebrate taxa in wealthier countries.

The redox fate of hydrogen peroxide in the marine water column - Kevin M. Sutherland; Kalina C. Grabb; Jennifer S. Karolewski; Lina Taenzer; Colleen M. Hansel; Scott D. Wankel (Limnology and Oceanography, 2021)
Marine microbes produce extracellular reactive oxygen species (ROS) such as superoxide and hydrogen peroxide (H 2 O 2 ) as a result of regulated and nonregulated physiological and metabolic reactions. ROS production can be a sink and cryptic recycling flux of dissolved oxygen that may rival other key fluxes in the global oxygen cycle; however, the low abundance and high turnover rate of ROS makes this figure difficult to constrain. One key step in determining the disparity between the gross production of ROS and the net sink of dissolved oxygen lies in understanding the degradation pathways of H 2 O 2 in the marine water column. In this study, we use isotope‐labeling techniques to determine the redox fate of H 2 O 2 in a range of marine environments off the West Coast of California. We find that H 2 O 2 reduction is greater than or equal to H 2 O 2 oxidation at most sampled depths, with notable exceptions in some surface and intermediate water depths. The observation that H 2 O 2 oxidation can exceed reduction in the dark ocean indicates the presence of an oxidizing decay pathway that is not among the known suite of microbially mediated enzymatic pathways (i.e., catalase and peroxidase), pointing to an abiotic and/or a nonenzymatic decay pathway at intermediate water depths. These results highlight the complexity and heterogeneity of ROS decay pathways in natural waters and their unconstrained regulation of oxygen levels within the ocean.

Correction to: Transmission of a novel predatory behaviour is not restricted to kin - Laura X. L. Tan; Wouter F. D. van Dongen; Craig D. H. Sherman; Kasun B. Ekanayake; Peter Dann; Duncan R. Sutherland; Michael A. Weston (Biological Invasions, 2021)

Transmission of a novel predatory behaviour is not restricted to kin - Laura X. L. Tan; Wouter F. D. van Dongen; Craig D. H. Sherman; Kasun B. Ekanayake; Peter Dann; Duncan R. Sutherland; Michael A. Weston (Biological Invasions, 2021)

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Ensuring tests of conservation interventions build on existing literature - William J. Sutherland; Sergio Ticul Alvarez‐Castañeda; Tatsuya Amano; Roberto Ambrosini; Philip Atkinson; John M. Baxter; Alexander L. Bond; Philip J. Boon; Katherine L. Buchanan; Jos Barlow; Giuseppe Bogliani; Olivia M. Bragg; et al. (Conservation Biology, 2020)

First record of Bonnemaisonia hamifera (Bonnemaisoniales, Rhodophyta) in the South Pacific, from the South Island of New Zealand - David J. Garbary; Roberta D’Archino; Brendan Flack; Christopher D. Hepburn; Wendy A. Nelson; Daniel Pritchard; Judy. E. Sutherland (New Zealand Journal of Marine and Freshwater Research, 2020)
The tetrasporophytic ‘ Trailliella ’ stage of the red algal genus Bonnemaisonia is reported for the first time from the Southern Hemisphere. Here we describe a bloom of the tetrasporophyte of B. hamifera from the mouth of the Waikouaiti River, Karitāne, South Island, where it occurred as thousands of free‐floating tufts up to 1 cm wide in shallow water, accumulated in windrows on sand banks and beaches, and in the water column at depths of 10–12 m on the adjacent open coast. Gametophytic stages have not yet been found in New Zealand. The material collected to date is strictly vegetative, and reproduction occurs via fragmentation. The identity of the New Zealand samples as B. hamifera was confirmed by both morphology and rbc L sequencing. The abundance and floating dispersal of B. hamifera suggests that it is invasive and will become widely distributed in New Zealand.

Genetic variants associated with exercise performance in both moderately trained and highly trained individuals - N. R. Harvey; S. Voisin; P. J. Dunn; H. Sutherland; X. Yan; M. Jacques; I. D. Papadimitriou; L. J. Haseler; K. J. Ashton; L. M. Haupt; N. Eynon; L. R. Griffiths (Molecular Genetics and Genomics, 2020)

Ebullition of oxygen from seagrasses under supersaturated conditions - Matthew H. Long; Kevin Sutherland; Scott D. Wankel; David J. Burdige; Richard C. Zimmerman (Limnology and Oceanography, 2020)
Gas ebullition from aquatic systems to the atmosphere represents a potentially important fraction of primary production that goes unquantified by measurements of dissolved gas concentrations. Although gas ebullition from photosynthetic surfaces has often been observed, it is rarely quantified. The resulting underestimation of photosynthetic activity may significantly bias the determination of ecosystem trophic status and estimated rates of biogeochemical cycling from in situ measures of dissolved oxygen. Here, we quantified gas ebullition rates in Zostera marina meadows in Virginia, U.S.A. using simple funnel traps and analyzed the oxygen concentration and isotopic composition of the captured gas. Maximum hourly rates of oxygen ebullition (3.0 mmol oxygen m −2 h −1 ) were observed during the coincidence of high irradiance and low tides, particularly in the afternoon when oxygen and temperature maxima occurred. The daily ebullition fluxes (up to 11 mmol oxygen m −2 d −1 ) were roughly equivalent to net primary production rates determined from dissolved oxygen measurements indicating that bubble ebullition can represent a major component of primary production that is not commonly included in ecosystem‐scale estimates. Oxygen content comprised 20–40% of the captured bubble gas volume and correlated negatively with its δ 18 O values, consistent with a predominance of mixing between the higher δ 18 O of atmospheric oxygen in equilibrium with seawater and the lower δ 18 O of oxygen derived from photosynthesis. Thus, future studies interested in the metabolism of highly productive, shallow water ecosystems, and particularly those measuring in situ oxygen flux, should not ignore the bubble formation and ebullition processes described here.

Triassic to Neogene tectono-magmatic events within Lorne Basin evolution, coastal New South Wales, eastern Australia - F. L. Sutherland; I. T. Graham; H. Zwingmann; D. J. Och; C. J. Gardner; R. E. Pogson; R. J. Griffiths; A. Lay (Australian Journal of Earth Sciences, 2020)

Evaluating toxicity risk in sediments after remediation at a Superfund megasite using a Triad approach - Amanda D. Harwood; Grace E. Sutherland; M. Megan Woller-Skar; Michael J. Lydy; Murray C. Borrello (Environmental Monitoring and Assessment, 2019)

Extracellular superoxide production by key microbes in the global ocean - Kevin M. Sutherland; Allison Coe; Rebecca J. Gast; Sydney Plummer; Christopher P. Suffridge; Julia M. Diaz; Jeff S. Bowman; Scott D. Wankel; Colleen M. Hansel (Limnology and Oceanography, 2019)
Bacteria and eukaryotes produce the reactive oxygen species superoxide both within and outside the cell. Although superoxide is typically associated with the detrimental and sometimes fatal effects of oxidative stress, it has also been shown to be involved in a range of essential biochemical processes, including cell signaling, growth, differentiation, and defense. Light‐independent extracellular superoxide production has been shown to be widespread among many marine heterotrophs and phytoplankton, but the extent to which this trait is relevant to marine microbial physiology and ecology throughout the global ocean is unknown. Here, we investigate the dark extracellular superoxide production of five groups of organisms that are geographically widespread and represent some of the most abundant organisms in the global ocean. These include Prochlorococcus , Synechococcus , Pelagibacter , Phaeocystis , and Geminigera . Cell‐normalized net extracellular superoxide production rates ranged seven orders of magnitude, from undetectable to 14,830 amol cell −1 h −1 , with the cyanobacterium Prochlorococcus being the lowest producer and the cryptophyte Geminigera being the most prolific producer. Extracellular superoxide production exhibited a strong inverse relationship with cell number, pointing to a potential role in cell signaling. We demonstrate that rapid, cell‐number–dependent changes in the net superoxide production rate by Synechococcus and Pelagibacter arose primarily from changes in gross production of extracellular superoxide, not decay. These results expand the relevance of dark extracellular superoxide production to key marine microbes of the global ocean, suggesting that superoxide production in marine waters is regulated by a diverse suite of marine organisms in both dark and sunlit waters.

A New Wavelet Method for Identification of Eddies and Assessment of Incidents on Islands of the Eastern Caribbean - Jason D. Tambie; Madiha Farag-Miller; Keith Miller; Bheshem Ramlal; Michael Sutherland (Marine Geodesy, 2019)

Range expansion of tropical pyrosomes in the northeast Pacific Ocean - Kelly R. Sutherland; Hilarie L. Sorensen; Olivia N. Blondheim; Richard D. Brodeur; Aaron W. E. Galloway (Ecology, 2018)

Standardized reporting of the costs of management interventions for biodiversity conservation - Gwenllian D. Iacona; William J. Sutherland; Bonnie Mappin; Vanessa M. Adams; Paul R. Armsworth; Tim Coleshaw; Carly Cook; Ian Craigie; Lynn V. Dicks; James A. Fitzsimons; Jennifer McGowan; Andrew J. Plumptre; et al. (Conservation Biology, 2018)
Effective conservation management interventions must combat threats and deliver benefits at costs that can be achieved within limited budgets. Considerable effort has focused on measuring the potential benefits of conservation interventions, but explicit quantification of the financial costs of implementation is rare. Even when costs have been quantified, haphazard and inconsistent reporting means published values are difficult to interpret. This reporting deficiency hinders progress toward a collective understanding of the financial costs of management interventions across projects and thus limits the ability to identify efficient solutions to conservation problems or attract adequate funding. We devised a standardized approach to describing financial costs reported for conservation interventions. The standards call for researchers and practitioners to describe the objective and outcome, context and methods, and scale of costed interventions, and to state which categories of costs are included and the currency and date for reported costs. These standards aim to provide enough contextual information that readers and future users can interpret the cost data appropriately. We suggest these standards be adopted by major conservation organizations, conservation science institutions, and journals so that cost reporting is comparable among studies. This would support shared learning and enhance the ability to identify and perform cost‐effective conservation.

Trophic ecology of the neustonic cnidarian Velella velella in the northern California Current during an extensive bloom year: insights from gut contents and stable isotope analysis - Samantha M. Zeman; Marco Corrales-Ugalde; Richard D. Brodeur; Kelly R. Sutherland (Marine Biology, 2018)

Asymmetries, heterosis, and phenotypic profiles of red junglefowl, White Plymouth Rocks, and F1 and F2 reciprocal crosses - D. A. T. Sutherland; C. F. Honaker; B. Dorshorst; L. Andersson; P. B. Siegel (Journal of Applied Genetics, 2018)

Political transition and emergent forest‐conservation issues in Myanmar - Graham W. Prescott; William J. Sutherland; Daniel Aguirre; Matthew Baird; Vicky Bowman; Jake Brunner; Grant M. Connette; Martin Cosier; David Dapice; Jose Don T. De Alban; Alex Diment; Julia Fogerite; et al. (Conservation Biology, 2017)
Political and economic transitions have had substantial impacts on forest conservation. Where transitions are underway or anticipated, historical precedent and methods for systematically assessing future trends should be used to anticipate likely threats to forest conservation and design appropriate and prescient policy measures to counteract them. Myanmar is transitioning from an authoritarian, centralized state with a highly regulated economy to a more decentralized and economically liberal democracy and is working to end a long‐running civil war. With these transitions in mind, we used a horizon‐scanning approach to assess the 40 emerging issues most affecting Myanmar's forests, including internal conflict, land‐tenure insecurity, large‐scale agricultural development, demise of state timber enterprises, shortfalls in government revenue and capacity, and opening of new deforestation frontiers with new roads, mines, and hydroelectric dams. Averting these threats will require, for example, overhauling governance models, building capacity, improving infrastructure‐ and energy‐project planning, and reforming land‐tenure and environmental‐protection laws. Although challenges to conservation in Myanmar are daunting, the political transition offers an opportunity for conservationists and researchers to help shape a future that enhances Myanmar's social, economic, and environmental potential while learning and applying lessons from other countries. Our approach and results are relevant to other countries undergoing similar transitions.

Prioritization of knowledge‐needs to achieve best practices for bottom trawling in relation to seabed habitats - Michel J Kaiser; Ray Hilborn; Simon Jennings; Ricky Amaroso; Michael Andersen; Kris Balliet; Eric Barratt; Odd A Bergstad; Stephen Bishop; Jodi L Bostrom; Catherine Boyd; Eduardo A Bruce; et al. (Fish and Fisheries, 2016)
Management and technical approaches that achieve a sustainable level of fish production while at the same time minimizing or limiting the wider ecological effects caused through fishing gear contact with the seabed might be considered to be ‘best practice’. To identify future knowledge‐needs that would help to support a transition towards the adoption of best practices for trawling, a prioritization exercise was undertaken with a group of 39 practitioners from the seafood industry and management, and 13 research scientists who have an active research interest in bottom‐trawl and dredge fisheries. A list of 108 knowledge‐needs related to trawl and dredge fisheries was developed in conjunction with an ‘expert task force’. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge‐need. The top 25 knowledge‐needs are presented, as scored separately by practitioners and scientists. There was considerable consistency in the priorities identified by these two groups. The top priority knowledge‐need to improve current understanding on the distribution and extent of different habitat types also reinforced the concomitant need for the provision and access to data on the spatial and temporal distribution of all forms of towed bottom‐fishing activities. Many of the other top 25 knowledge‐needs concerned the evaluation of different management approaches or implementation of different fishing practices, particularly those that explore trade‐offs between effects of bottom trawling on biodiversity and ecosystem services and the benefits of fish production as food.

Prioritization of knowledge needs for sustainable aquaculture: a national and global perspective - Aisla C Jones; Angela Mead; Michel J Kaiser; Melanie C V Austen; Alex W Adrian; Neil A Auchterlonie; Kenneth D Black; Lucy R Blow; Charlotte Bury; Janet H Brown; Gavin M Burnell; Elaine Connolly; et al. (Fish and Fisheries, 2015)
Aquaculture is currently the fastest expanding global animal food production sector and is a key future contributor to food security. An increase in food security will be dependent upon the development and improvement of sustainable practices. A prioritization exercise was undertaken, focusing on the future knowledge needs to underpin UK sustainable aquaculture (both domestic and imported products) using a ‘task force’ group of 36 ‘practitioners’ and 12 ‘research scientists’ who have an active interest in sustainable aquaculture. A long list of 264 knowledge needs related to sustainable aquaculture was developed in conjunction with the task force. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge need. The top 25 knowledge needs are presented, as scored separately by ‘practitioners’ or ‘research scientists’. There was similar agreement in priorities identified by these two groups. The priority knowledge needs will provide guidance to structure ongoing work to make science accessible to practitioners and help to prioritize future science policy needs and funding. The process of knowledge exchange, and the mechanisms by which this can be achieved, effectively emerged as the top priority for sustainable aquaculture. Viable alternatives to wild fish‐based aquaculture feeds, resource constraints that will potentially limit expansion of aquaculture, sustainable offshore aquaculture and the treatment of sea lice also emerged as strong priorities. Although the exercise was focused on UK needs for sustainable aquaculture, many of the emergent issues are considered to have global application.

Patterns of River Influence and Connectivity Among Subbasins of Puget Sound, with Application to Bacterial and Nutrient Loading - N. S. Banas; L. Conway-Cranos; D. A. Sutherland; P. MacCready; P. Kiffney; M. Plummer (Estuaries and Coasts, 2015)

Markers for seedling and adult plant crown rot resistance in four partially resistant bread wheat sources - A. Martin; W. D. Bovill; C. D. Percy; D. Herde; S. Fletcher; A. Kelly; S. M. Neate; M. W. Sutherland (Theoretical and Applied Genetics, 2015)

Surface Salinity in the North Atlantic Subtropical Gyre During the STRASSE/SPURS Summer 2012 Cruise - Gilles Reverdin; Simon Morisset; Louis Marieé; Denis Bourras; Graigory Sutherland; Brian Ward; Joaquin Salvador; Jordi Font; Yannis Cuypers; Luca Centorioni; Verena Hormann; Nicolas Koldziejczyk; et al. (Oceanography, 2015)

A demographic, spatially explicit patch occupancy model of metapopulation dynamics and persistence - C. S. Sutherland; D. A. Elston; X. Lambin (Ecology, 2014)
Patch occupancy models are extremely important and popular tools for understanding the dynamics, and predicting the persistence, of spatially structured populations. Typically this endeavor is facilitated either by models from classic metapopulation theory focused on spatially explicit, dispersal‐driven colonization–extinction dynamics and generally assuming perfect detection, or by more recent hierarchical site occupancy models that account for imperfect detection but rarely include spatial effects, such as dispersal, explicitly. Neither approach explicitly considers local demographics in a way that can be used for future projections. However, despite being arguably of equal importance, dispersal and connectivity, local demography, and imperfect detection are rarely modeled explicitly and simultaneously. Understanding the spatiotemporal occurrence patterns of spatially structured populations and making biologically realistic long‐term predictions of persistence would benefit from the simultaneous treatment of space, demography, and detectability. We integrated these key ideas in a tractable and intuitive way to develop a demographic and spatially realistic patch occupancy model that incorporates components of dispersal, local demographic stage‐structure, and detectability. By explicitly relating stage‐specific abundances to measurable patch properties, biologically realistic projections of long‐term metapopulation dynamics could be made. We applied our model to data from a naturally fragmented population of water voles Arvicola amphibius to describe observed patch occupancy dynamics and to investigate long‐term persistence under scenarios of elevated stage‐specific local extinction. Accounting for biases induced by imperfect detection, we were able to estimate: stable, and higher than observed metapopulation occupancy; high rates of patch turnover and stage‐specific colonization and extinction rates (juvenile and adult, respectively); and juvenile dispersal distances (average 2.10 km). We found that metapopulation persistence in the presence of elevated extinction risk differed depending on which life stage was exposed, and was more sensitive to elevated juvenile rather than adult extinction risk. Predictions of persistence when dynamics are stage‐specific suggest that metapopulations may be more resilient to changes in the environment than predicted when relationships are based on patch size approximations rather than population sizes. Our approach allows explicit consideration of local dynamics and dispersal in spatially structured and stage‐structured populations, provides a more detailed mechanistic understanding of metapopulation functioning, and can be used to investigate future extinction risk under biologically meaningful scenarios.

The alternative splicing of the apolipoprotein E gene is unperturbed in the brains of Alzheimer’s disease patients - James D. Mills; Pamela J. Sheahan; Donna Lai; Jillian J. Kril; Michael Janitz; Greg T. Sutherland (Molecular Biology Reports, 2014)

Conversion of Biosynthetic Precursors of RNA to Those of DNA by Photoredox Chemistry - Dougal J. Ritson; John D. Sutherland (Journal of Molecular Evolution, 2014)

High rate algal pond systems for low‐energy wastewater treatment, nutrient recovery and energy production - R Craggs; J Park; S Heubeck; D Sutherland (New Zealand Journal of Botany, 2014)
High rate algal pond (HRAP) systems provide opportunities for low‐energy wastewater treatment and energy recovery from wastewater solids, as well as biofuel production from the harvested algal biomass. The wastewater is pretreated using covered anaerobic ponds or gravity settlers and covered digester ponds which remove and digest the wastewater solids. The effluent is then treated in shallow gently mixed HRAP which efficiently breakdown the dissolved organic matter. The algae assimilate wastewater nutrients to provide both secondary and partial tertiary‐level treatment. HRAP also provide more efficient natural disinfection. HRAP performance can be further enhanced by bubbling CO 2 into the pond during the day to promote algal growth when it is often carbon‐limited. This paper discusses the design and operation and performance of HRAP systems and their application for economical, low‐energy upgrade of conventional wastewater treatment ponds combined with energy recovery and biofuel production.

Multiple felsic events within post-10 Ma volcanism, Southeast Australia: inputs in appraising proposed magmatic models - F. L. Sutherland; I. T. Graham; J. D. Hollis; S. Meffre; H. Zwingmann; F. Jourdan; R. E. Pogson (Australian Journal of Earth Sciences, 2014)

BDNF and TNF-α polymorphisms in memory - B. S. Yogeetha; L. M. Haupt; K. McKenzie; H. G. Sutherland; R. K. Okolicsyani; R. A. Lea; B. H. Maher; R. C. K. Chan; D. H. K. Shum; L. R. Griffiths (Molecular Biology Reports, 2013)

QTLs for water absorption and flour yield identified in the doubled haploid wheat population Lang/QT8766 - G. P. Fox; A. Martin; A. M. Kelly; M. W. Sutherland; D. Martin; P. M. Banks; J. Sheppard (Euphytica, 2013)

Symptom development proceeds at different rates in susceptible and partially resistant cereal seedlings infected with Fusarium pseudograminearum - C. D. Percy; G. B. Wildermuth; M. W. Sutherland (Australasian Plant Pathology, 2012)

Epidemiology of non-multiresistant methicillin-resistant Staphylococcus aureus infection in Queensland, Australia: associations with indigenous populations and Panton–Valentine leukocidin - G. R. Nimmo; J. M. Schooneveldt; J. L. Sutherland; S. Power; D. Olesen; C. Selvey; F. Beard; M. Jones; D. L. Paterson (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Pyramiding QTL increases seedling resistance to crown rot (Fusarium pseudograminearum) of wheat (Triticum aestivum) - W. D. Bovill; M. Horne; D. Herde; M. Davis; G. B. Wildermuth; M. W. Sutherland (Theoretical and Applied Genetics, 2010)

Forensic DNA confirms intraguild killing of a chuditch (Dasyurus geoffroii) by a feral cat (Felis catus) - A. S. Glen; O. Berry; D. R. Sutherland; S. Garretson; T. Robinson; P. J. de Tores (Conservation Genetics, 2010)

Pramipexole effects on startle gating in rats and normal men - Neal R. Swerdlow; Sophia A. Lelham; Ashley N. Sutherland Owens; Wei-Li Chang; Sebastiaan D. T. Sassen; Jo A. Talledo (Psychopharmacology, 2009)

One Hundred Questions of Importance to the Conservation of Global Biological Diversity - W. J. SUTHERLAND; W. M. ADAMS; R. B. ARONSON; R. AVELING; T. M. BLACKBURN; S. BROAD; G. CEBALLOS; I. M. CÔTÉ; R. M. COWLING; G. A. B. DA FONSECA; E. DINERSTEIN; P. J. FERRARO; et al. (Conservation Biology, 2009)
We identified 100 scientific questions that, if answered, would have the greatest impact on conservation practice and policy. Representatives from 21 international organizations, regional sections and working groups of the Society for Conservation Biology, and 12 academics, from all continents except Antarctica, compiled 2291 questions of relevance to conservation of biological diversity worldwide. The questions were gathered from 761 individuals through workshops, email requests, and discussions. Voting by email to short‐list questions, followed by a 2‐day workshop, was used to derive the final list of 100 questions. Most of the final questions were derived through a process of modification and combination as the workshop progressed. The questions are divided into 12 sections: ecosystem functions and services, climate change, technological change, protected areas, ecosystem management and restoration, terrestrial ecosystems, marine ecosystems, freshwater ecosystems, species management, organizational systems and processes, societal context and change, and impacts of conservation interventions. We anticipate that these questions will help identify new directions for researchers and assist funders in directing funds.

Spatial and Temporal Modeling of Beach Use: A Case Study of East Anglia, UK - E. G. Coombes; A. P. Jones; I. J. Bateman; J. A. Tratalos; J. A. Gill; D. A. Showler; A. R. Watkinson; W. J. Sutherland (Coastal Management, 2009)

Elevated Blood-lead Levels in First Nation People of Northern Ontario Canada: Policy Implications - L. J. S. Tsuji; B. C. Wainman; I. D. Martin; J.-P. Weber; C. Sutherland; E. N. Liberda; E. Nieboer (Bulletin of Environmental Contamination and Toxicology, 2008)

Assembling a mutualism: ant symbionts locate their host plants by detecting volatile chemicals - D. P. Edwards; M. Hassall; W. J. Sutherland; D. W. Yu (Insectes Sociaux, 2006)

Effectiveness of a Coral-Derived Surfacing Material for Reducing Sediment Production on Unpaved Roads, Schoffield Barracks, Oahu, Hawaii - Alan D. Ziegler; Ross A. Sutherland (Environmental Management, 2006)

A QTL located on chromosome 4A associated with dormancy in white- and red-grained wheats of diverse origin - D. Mares; K. Mrva; J. Cheong; K. Williams; B. Watson; E. Storlie; M. Sutherland; Y. Zou (Theoretical and Applied Genetics, 2005)

Elevated Levels of PCBs in First Nation Communities of the Western James Bay Region of Northern Ontario, Canada: The Use of Correspondence Analysis to Identify Source of Exposure - L. J. S. Tsuji; B. C. Wainman; I. D. Martin; J.-P. Weber; C. Sutherland; E. Nieboer (Bulletin of Environmental Contamination and Toxicology, 2005)

Growth, productivity, and competitiveness of introgressed weedy Brassica rapa hybrids selected for the presence of Bt cry1Ac and gfp transgenes - MATTHEW D. HALFHILL; JAMIE P. SUTHERLAND; HONG SEOK MOON; GUY M. POPPY; SUZANNE I. WARWICK; ARTHUR K. WEISSINGER; THOMAS W. RUFTY; PAUL L. RAYMER; C. NEAL STEWART (Molecular Ecology, 2005)
Concerns exist that transgenic crop × weed hybrid populations will be more vigorous and competitive with crops compared with the parental weed species. Hydroponic, glasshouse, and field experiments were performed to evaluate the effects of introgression of Bacillus thuringiensis (Bt) cry1Ac and green fluorescent protein (GFP) transgenes on hybrid productivity and competitiveness in four experimental Brassica rapa × transgenic Brassica napus hybrid generations (F 1 , BC 1 F 1 , BC 2 F 1 and BC 2 F 2 ). The average vegetative growth and nitrogen (N) use efficiency of transgenic hybrid generations grown under high N hydroponic conditions were lower than that of the weed parent ( Brassica rapa , AA, 2n = 20), but similar to the transgenic crop parent, oilseed rape ( Brassica napus , AACC, 2n = 38). No generational differences were detected under low N conditions. In two noncompetitive glasshouse experiments, both transgenic and nontransgenic BC 2 F 2 hybrids had on average less vegetative growth and seed production than B. rapa . In two high intraspecific competition field experiments with varied herbivore pressure, BC 2 F 2 hybrids produced less vegetative dry weight than B. rapa . The competitive ability of transgenic and nontransgenic BC 2 F 2 hybrids against a neighbouring crop species were quantified in competition experiments that assayed wheat ( Triticum aestivum ) yield reductions under agronomic field conditions. The hybrids were the least competitive with wheat compared with parental Brassica competitors, although differences between transgenic and nontransgenic hybrids varied with location. Hybridization, with or without transgene introgression, resulted in less productive and competitive populations.

LUCA-15/RBM5, a putative tumour suppressor, enhances multiple receptor-initiated death signals - N. D. Rintala-Maki; L. C. Sutherland (Apoptosis, 2004)

Influence of zinc and iron enrichments on phytoplankton growth in the northeastern subarctic Pacific - D. W. Crawford; M. S. Lipsen; D. A. Purdie; M. C. Lohan; P. J. Statham; F. A. Whitney; J. N. Putland; W. K. Johnson; N. Sutherland; T. D. Peterson; P. J. Harrison; C. S. Wong (Limnology and Oceanography, 2003)
Near‐surface seawater from the northeastern subarctic Pacific was incubated on deck for 8 d, supplemented with (1) control, no additions (2) +Zn (3) +Fe (4) +Zn+Fe. Concentrations of total Zn and Fe at time zero (t 0 ) and in the control remained at ~0.1–0.2 nmol L −1 . In the control, chlorophyll (=0.3 mg m −3 ), 14 C uptake into POC and PIC, and inorganic nutrients all remained relatively constant. Addition of Zn slightly but significantly increased chlorophyll ( p = 0.05), decreased phosphate (p = 0.01) and nitrate (p = 0.05), and in P versus E experiments, increased P m >10‐fold and P m chl 2–3‐fold. The abundance of small diatoms and coccolithophores was higher in the +Zn treatment compared to the control. The +Fe and +Zn+Fe treatments, compared to the control, both showed >10‐fold increases in chlorophyll and 14 C uptake into POC and PIC and complete removal of nitrate (≤0.2 mmol m −3 ). However, differences were observed in size‐fractionated data; the +Zn+Fe treatment had significantly lower percent chlorophyll in the >20‐ µm fraction (p = 0.01) and a higher percentage in the 0.2–5‐ µm fraction (p = 0.01) than the +Fe treatment. In P versus E experiments, both +Fe treatments increased P m and α around 100‐fold and P m chl and α chl by 5–10‐fold compared to the control. The +Fe treatment showed a slightly higher α chl and slightly lower P m chl than the +Zn+Fe treatment. Abundance of large diatoms, small diatoms, small flagellates, and coccol‐ chl m ithophores all increased substantially (~7–1,000‐fold) in response to Fe addition, whereas dinoflagellate abundance only doubled. The +Zn+Fe treatment had higher abundances of small diatoms and small flagellates than the +Fe treatment. We conclude that Zn additions had limited influence on conventional indices of phytoplankton growth compared to Fe, but that there might be subtle influences of Zn that require further attention.

Effect of Film-forming Polymers on Infection of Barley with the Powdery Mildew Fungus, Blumeria graminis f. sp. hordei - F. Sutherland; D. R. Walters (European Journal of Plant Pathology, 2002)

Adaptive host choice and avoidance of superparasitism in the spawning decisions of bitterling ( Rhodeus sericeus ) - C. Smith; John D. Reynolds; William J. Sutherland; Pavel Jurajda (Behavioral Ecology and Sociobiology, 2000)

Reactivation of heritably silenced gene expression in mice - Heidi G.E. Sutherland; Margot Kearns; Hugh D. Morgan; Alexander P. Headley; Christine Morris; David I.K. Martin; Emma Whitelaw (Mammalian Genome, 2000)

Detection of a novel missense mutation and second recurrent mutation in the CACNA1A gene in individuals with EA-2 and FHM - K.L. Friend; D. Crimmins; T.G. Phan; C.M. Sue; A. Colley; V.S.C. Fung; J.G.L. Morris; G.R. Sutherland; R.I. Richards (Human Genetics, 1999)

Detection of a novel missense mutation and second recurrent mutation in the CACNA1A gene in individuals with EA-2 and FHM - K.L. Friend; D. Crimmins; T.G. Phan; C.M. Sue; A. Colley; V.S.C. Fung; J.G.L. Morris; G.R. Sutherland; R.I. Richards (Human Genetics, 1999)

Biodegradation of crosslinked acrylic polymers by a white-rot fungus - Greg R. J. Sutherland; Joachim Haselbach; Steven D. Aust (Environmental Science and Pollution Research, 1997)

Akinetes of the cyanobacteriumNostoc PCC 7524: morphological changes during synchronous germination - Joan M. Sutherland; William D. P. Stewart; Michael Herdman (Archives of Microbiology, 1985)

Toxicity-metabolism relationship of the photoisomers of certain chlorinated cyclodiene insecticide chemicals - M. A. Q. Khan; R. H. Stanton; D. J. Sutherland; J. D. Rosen; N. Maitra (Archives of Environmental Contamination and Toxicology, 1973)